Flexural Performance of Emulsified-Asphalt-Modified ECC for Expansion Joint Use - Quan Mao; Zhigang Zhang; Hui Ma (Advances in Civil Engineering)
The concrete transition zone plays an important role in bridge expansion joint structure, which provides a good connection between the expansion joint installation and bridge decks. However, the premature deteriorations of concrete transition zone are found to be the major diseases of expansion joint during service life. Therefore, a material with high ductility, superior durability, and low modulus/stiffness is highly desired for transition zone. Engineering cementitious composites (ECC), a kind of high-performance concrete featuring the prominent ductility and durability, are a promising material for transition zone of expansion joint. This paper introduces a specific ECC material for transition zone, which is modified by emulsified asphalt (EA-ECC), and has the high deformation ability and low modulus/stiffness. The flexural mechanical properties including flexural stress-load displacement relation, flexural secant stiffness, and elastic modulus of the EA-ECC’s matrix were investigated experimentally. The microstructures of EA-ECC were observed via scanning electron microscope (SEM) imaging. Additionally, the influence of test temperature on flexural mechanical properties of EA-ECC was also investigated. It is found that the ultimate flexural stress of EA-ECC reduces gradually with increasing EA content. Conversely, the flexural deformation capacity shows an increasing trend with EA content. Additionally, incorporating EA significantly reduces the flexural secant stiffness and elastic modulus of EA-ECCs. The research results concluded that incorporating EA in ECC can significantly improve the flexural deformation ability accompanied by relatively lower modulus, which is likely to reduce the impact load on transition zone caused by vehicle bumping and prolong the service life of the whole bridge expansion joint structure.